2016
DOI: 10.1136/bmjopen-2015-009688
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with presenting late or with advanced HIV disease in the Netherlands, 1996–2014: results from a national observational cohort

Abstract: ObjectivesEarly testing for HIV and entry into care are crucial to optimise treatment outcomes of HIV-infected patients and to prevent spread of HIV. We examined risk factors for presentation with late or advanced disease in HIV-infected patients in the Netherlands.MethodsHIV-infected patients registered in care between January 1996 and June 2014 were selected from the ATHENA national observational HIV cohort. Risk factors for late presentation and advanced disease were analysed by multivariable logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 26 publications
(23 reference statements)
9
59
1
Order By: Relevance
“…Unfortunately, more than three decades after the HIV epidemic started, many patients all over the world are still diagnosed very late in the course of their disease: in a recent Dutch paper, it was found that more than half of their patients were diagnosed late with HIV disease and 35% of their cohort were diagnosed with AHD 18. Similar rates of late diagnosis are present all over Europe 19.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, more than three decades after the HIV epidemic started, many patients all over the world are still diagnosed very late in the course of their disease: in a recent Dutch paper, it was found that more than half of their patients were diagnosed late with HIV disease and 35% of their cohort were diagnosed with AHD 18. Similar rates of late diagnosis are present all over Europe 19.…”
Section: Discussionmentioning
confidence: 99%
“…A late‐stage diagnosis of HIV has negative consequences for the individual and society such as increased morbidity and mortality, poorer response to treatment, higher healthcare costs and increased transmission to others . Risk factors for late diagnosis include older age, female gender and identifying as heterosexual . Late‐stage diagnoses are often made in individuals who have presented previously to healthcare services with potential HIV‐related symptoms and signs .…”
Section: Introductionmentioning
confidence: 99%
“…8 These barriers result in women being diagnosed later in their infection in countries with a low HIV prevalence among the general population and where women have not traditionally been considered a key risk population. [9][10][11][12] New HIV diagnoses among women in Australia make up approximately 10% of all diagnoses and, among the estimated 26,444 people living with HIV in Australia in 2016, 12% were women. In Australia, a disproportionate rate of HIV diagnosis exists Two decades of surveillance data show late presentation among a diverse group of women diagnosed with HIV in Victoria, Australia among Aboriginal and migrant women compared with non-Aboriginal Australianborn women.…”
mentioning
confidence: 99%